Fluoxetine Potentiates Phagocytosis and Autophagy in Microglia - Park, Sung Hee; Lee, Young-Sun; Yang, Hyun-Jeong; Song, Gyun Jee (Frontiers in Pharmacology, 2021)
Fluoxetine is a classic antidepressant drug, and its immunomodulatory effects have recently been reported in many disease models. In addition, it has strong anti-neuroinflammatory effects in stroke and neurodegenerative animal models. However, the effect of fluoxetine on microglia phagocytosis and its molecular mechanisms have not yet been studied. In this study, we investigated whether fluoxetine has a regulatory effect on microglial function. Microglia cell lines and primary mouse microglia were treated with fluoxetine, and the production of inflammatory cytokines and neurotrophic factors and the phagocytosis of amyloid beta were measured. Fluoxetine significantly attenuated the production of LPS-induced pro-inflammatory cytokines and oxidative stress in microglia. Fluoxetine also significantly potentiated microglia phagocytosis and autophagy. In addition, autophagy flux inhibitors attenuated fluoxetine-induced phagocytosis. In conclusion, fluoxetine induces autophagy and potentiates phagocytosis in microglia, which can be a novel molecular mechanism of the neuroinflammatory and neuroprotective effects of fluoxetine.